The Alternation u / o, Diphthongs, Pataḥ Furtivum and the 3m. s.Pronominal Suffix in Samaritan Hebrew and Aramaic Versus Tiberian Hebrew - Florentin, Moshe (Journal of Semitic studies, 2009)
Samaritan Hebrew and Aramaic, though sharing the same phonetic structure, differ mainly in the choice of options available in the general Samaritan pronunciation. In the present study we have argued that the use of the auxiliary vowel in general, and specifically the use of the pataḥ furtivum was relatively widespread in Samaritan Hebrew and relatively rare in Samaritan Aramaic. Only this fact caused the large distribution of the vowel u in an open post-tonic syllable in SH versus the clear preference of the vowel o in this position in SamaritanAramaic.Morpho-phonemic — alongside historical — analysis was used thoroughly in this short study. It helped us to prove that: (1) the vowel o of the 3m. s. attached to a plural noun in SH — e.g. sūso — is genuine in this language, being underlyingly a closed syllable; (2) the reason for the retention of the diphthong .åw in the same pronominal suffix in Tiberian Hebrew — e.g. sūsåw — is purely phonetic, i.e. the long vowel before the semi-vowel (*sūsāw).